9m-25=-13+5m

Simple and best practice solution for 9m-25=-13+5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m-25=-13+5m equation:


Simplifying
9m + -25 = -13 + 5m

Reorder the terms:
-25 + 9m = -13 + 5m

Solving
-25 + 9m = -13 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
-25 + 9m + -5m = -13 + 5m + -5m

Combine like terms: 9m + -5m = 4m
-25 + 4m = -13 + 5m + -5m

Combine like terms: 5m + -5m = 0
-25 + 4m = -13 + 0
-25 + 4m = -13

Add '25' to each side of the equation.
-25 + 25 + 4m = -13 + 25

Combine like terms: -25 + 25 = 0
0 + 4m = -13 + 25
4m = -13 + 25

Combine like terms: -13 + 25 = 12
4m = 12

Divide each side by '4'.
m = 3

Simplifying
m = 3

See similar equations:

| 3(4x-9)=51 | | -2/5x+3/8 | | -11+y/8=5 | | exp(6-4x)=1596 | | x/5=x/8+3 | | 3=10/3x-7 | | 3/m/12=4 | | 2+3=2m | | (7p+5q)(7p-5q)=0 | | 3x+y=91 | | 2x^2-5x-3=15 | | 15n-4-14n-13=-15 | | -4(x)(x)+19x=-30 | | 2m+16=3m+10 | | -2+8n=-26 | | 3-m/12=4 | | 5(3+5x)-3=112 | | 34-3a=5a-14 | | 5(2x-3)=7 | | -4x+19x=-30 | | 5-1/2(x+3)=66 | | -4x+19x=30 | | -4x+19x=39 | | -4y+1=-5y+8 | | 99x+24=1.49x | | (3x+2y)(3x-2y)=0 | | 7n+11=24+3n | | 7p+8=17+6p | | 19-9-220=1 | | 2-3x-7=x | | 3.9x-4=2.9x | | 3/8x-3=9 |

Equations solver categories